SYNCHROTRON-BASED INFRARED MICROSPECTROSCOPY AS A USEFUL TOOL TO STUDY HYDRATION STATES OF METEORITE CONSTITUENTS - Moroz L.V.; Schmidt M.; Schade U.; Hiroi T.; Ivanova M.A. (My University, 2006)
We present the results of the infrared (IR) microscopic study of the anomalous carbonaceous chondrites Dhofar (Dho) 225 and Dhofar 735 in comparison to typical CM2 chondrites Cold Bokkeveld, Murray, and Mighei. The Fourier transform infrared (FTIR) 2.5-14 μm reflectance measurements were performed on conventional polished sections using an infrared microscope with a synchrotron radiation source. We demonstrate that the synchrotron-based IR microspectroscopy is a useful, nondestructive tool for studying hydration states of meteorite constituents in situ. Our results show that the matrices of Dho 225 and Dho 735 are dehydrated compared to the matrices of typical CM2 chondrites. The spectra of the Dho 225 and Dho 735 matrices lack the 2.7-2.8 μm absorption feature present in the spectra of Cold Bokkeveld, Murray, and Mighei. Spectral signatures caused by Si-O vibrations in fine-grained, Fe-rich olivines dominate the 10 μm spectral region in the spectra of Dho 225 and Dho 735 matrices, while the spectra of normal CM2 chondrites are dominated by spectral signatures due to Si-O vibrations in phyllosilicates. We did not detect any hydrated phases in the spectra of Dho 225 and Dho 735 polished sections. In addition, the near-infrared reflectance spectra of Dho 225 and Dho 735 bulk powders show spectral similarities to the Antarctic metamorphosed carbonaceous chondrites. We confirm the results of previous mineralogical, chemical, and isotopic studies indicating that the two meteorites from Oman are the first non-Antarctic metamorphosed carbonaceous chondrites. © The Meteoritical Society, 2006.